2022
DOI: 10.1097/md.0000000000030808
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of surgical outcomes in 102 patients with renal cell carcinoma with venous tumor thrombus: A retrospective observational single-center study

Abstract: The aim of the study was to assess short-and long-term results following radical nephrectomy with renal vein and inferior vena cava thrombectomy in patients with renal cell cancer with venous thrombus and to investigate impact of various demographical, clinical and histological factors on overall survival (OS). The medical records of 102 adult patients with renal cell cancer with venous thrombus admitted for surgery in Department of General, Vascular and Transplant Surgery from 2012 to 2019 were retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…[13][14][15][16] The true estimate of patients with RCC and vena cava involvement with simultaneous vena cava wall invasion is unknown, with the majority of the studies being primarily clinical. 17,18 However, Rodriguez Faba et al 19 found that 21% of patients with RCC and tumor venous extension had microscopic vena cava wall invasion in their study. Our clinicopathologic study revealed that 45% of our patients with vena cava tumor thrombi had definitive evidence of vena cava wall microinvasion, which is higher than previously reported in a study done at our institution that reviewed patients from 2006 to 2014.…”
Section: Discussionmentioning
confidence: 84%
“…[13][14][15][16] The true estimate of patients with RCC and vena cava involvement with simultaneous vena cava wall invasion is unknown, with the majority of the studies being primarily clinical. 17,18 However, Rodriguez Faba et al 19 found that 21% of patients with RCC and tumor venous extension had microscopic vena cava wall invasion in their study. Our clinicopathologic study revealed that 45% of our patients with vena cava tumor thrombi had definitive evidence of vena cava wall microinvasion, which is higher than previously reported in a study done at our institution that reviewed patients from 2006 to 2014.…”
Section: Discussionmentioning
confidence: 84%
“…Among the eligible publications selected for this systematic review, when considered as a binomial variable, the postoperative renal insu ciency was present at least from 0.7% to 53.9% [18][19][20][21][22][23][24][25][26][27][28]. Additionally, in seven cohorts, postoperative AKI was present in a maximum of 53.9% of patients as reported by the study from Shin et al[26] (Table 4).…”
mentioning
confidence: 99%